Barra Boydell and Kerry Houston (eds), Music, Ireland and the Seventeenth Century, Irish Musical Studies, 10 (2009) - Holman, Peter (Journal of the Society for Musicology in Ireland, 2010)
Review of Barra Boydell and Kerry Houston (eds), Music, Ireland and the Seventeenth Century, Irish Musical Studies, 10 (Dublin: Four Courts Press, 2009), ISBN 978-1-84682-140-0